Design dan Fabrikasi Antena Fraktal Sierpinski Gasket 2,4 Ghz Single Patch Segitiga - Andik Atmaja; Deta Fitri Sulistiono; Nahdia B Rahardjo (Universitas Islam Lamongan, 2021)
In using wifi, an antenna that is relatively small and cheaper is needed. One of the specific antennas is the microstrip antenna. By using the microstrip fractal sierpinski gasket antenna form the microstrip antenna can increase the wifi signal and wider its bandwidth. In this research, a microstrip antenna is designed and made in the form of a microstrip fractal sierpinski gasket which will be used as a wifi receiver. The measurement results of the microstrip fractal sierpinski gasket antenna show that the antenna can work optimally with a frequency of 2.42 GHz, has a return loss value of -24.95 dB, a VSWR value of 1.122, a bandwidth value of 0.019 GHz.